Effects of tempol, a free radical scavenger, on long-term hyperdynamic porcine bacteremia - Matejovic, Martin; Krouzecky, Ales; Martinkova, Vendula; Rokyta, Richard; Radej, Jaroslav; Kralova, Hana; Treska, Vladislav; Radermacher, Peter; Novak, Ivan (Critical care medicine, 2005)
OBJECTIVES: Pretreatment with tempol, a membrane-permeable radical scavenger, has been shown to be protective in rodent models of endotoxic and Gram-positive shock. However, neither the pretreatment design nor hypodynamic endotoxic shock in rodents mimics the clinical scenario. Therefore, we investigated the effects of tempol in a posttreatment model of long-term, volume-resuscitated, hyperdynamic porcine bacteremia. DESIGN: Prospective, randomized, controlled experimental study. SETTING: University animal laboratory. SUBJECTS: Sixteen anesthetized, mechanically ventilated, and instrumented pigs. INTERVENTIONS: Sepsis was induced and maintained for 24 hrs with continuous infusion of live Pseudomonas aeruginosa. After 12 hrs of hyperdynamic sepsis, animals were randomized to receive either vehicle (control, n = 8) or continuous infusion of tempol (n = 8, 30 mg/kg/hr). MEASUREMENTS AND MAIN RESULTS: Systemic and hepatosplanchnic hemodynamics, oxygen exchange, metabolism, ileal mucosal microcirculation, and tonometry as well as oxidative stress and coagulation variables were assessed before and after 12, 18, and 24 hrs of P. aeruginosa infusion. Tempol significantly attenuated reduction in mean arterial pressure. Despite comparable mesenteric macrocirculation, tempol attenuated the otherwise progressive deterioration in ileal mucosal microcirculation and prevented mucosal acidosis. By contrast, treatment with tempol failed to influence the P. aeruginosa-induced derangements of hepatosplanchnic redox state, liver lactate clearance, and regional acidosis but prevented the development of renal dysfunction. In addition, tempol reduced nitrosative stress without significant effect on the gradual increase in plasma 8-isoprostanes. Finally, tempol attenuated sepsis-induced endothelial (von Willebrand factor) and hemostatic dysfunction (thrombin-antithrombin complexes, plasminogen activator inhibitor-type 1). CONCLUSIONS: The radical scavenger tempol partially prevented live bacteria from causing key features of hemodynamic and metabolic derangements in porcine hyperdynamic sepsis and beneficially affected surrogate markers of sepsis-induced endothelial and coagulation dysfunction. Incomplete reduction of oxidative stress because of dilutional effects and/or missed optimal therapeutic window for antioxidant treatment when used in posttreatment approach may account for the only partial protection by tempol in this model.
Keywords: energetický metabolismus; spinové značení; prasata; oxidační stres; Swine; antioxidancia; Male; Heart Rate; Cyclic N-Oxides; mužské pohlaví; srdeční frekvence; cyklické N-oxidy; Spin Labels; Animals; Energy Metabolism; krevní tlak; ženské pohlaví; játra; Antioxidants; zvířata; hemokoagulace; bakteriemie; Blood Pressure; Bacteremia; mikrocirkulace; Liver; Female; Oxidative Stress; Microcirculation; Blood Coagulation